Experience from Asian centers in a named-patient-use program for afatinib in patients with advanced non-small-cell lung cancer who had progressed following prior therapies, including patients with uncommon EGFR mutations - Chang, Gee-Chen (SPRINGER JAPAN KK, 2022)
10.1007/s10147-021-01869-0